2018
DOI: 10.3390/ijerph15040659
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Job Strain and Arterial Stiffness: A Large Survey among Enterprise Employees from Thailand

Abstract: As an intermediate endpoint to cardiovascular disease, arterial stiffness has received much attention recently. So far, the research on work stress and arterial stiffness is still sparse and inconsistent, and no investigations on work stress and cardiovascular health among the Thai working population have been reported. Therefore, we conducted an epidemiological study among 2141 Thai enterprise employees (858 men and 1283 women) who were free from any diagnosed cardiovascular disease. Work stress was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Furthermore, OPA may be a marker of poor psychosocial conditions, however, the association between OPA and nBRS remained after adjustment for education and perceived stress. Work stressors such as effortreward imbalance or demand-control imbalance could also be involved but were not measured in the current study (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, OPA may be a marker of poor psychosocial conditions, however, the association between OPA and nBRS remained after adjustment for education and perceived stress. Work stressors such as effortreward imbalance or demand-control imbalance could also be involved but were not measured in the current study (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Work stressors, such as effortreward imbalance or demand-control imbalance, could also be involved but were not measured in the current study. 30,31 Only a few prior studies have examined the association of SPA with nBRS and mBRS. They included small sample populations and used invasive methods to measure BRS (infusion of vasoactive drugs).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that albuminuria is often followed by the development and progression of aortic stiffness and atherosclerosis [33]. Finally, job strain was significantly associated with arterial stiffness in men among enterprise employees from Thailand [34]. In this study, we did not record occupations and labour levels.…”
Section: Discussionmentioning
confidence: 86%
“…The strengths of our study include having a relatively large number of participants with varying occupational backgrounds as earlier studies have concluded that manual workers may be more vulnerable to job strain induced high blood pressure [22], a strong correlate of arterial stiffness. Moreover, we used carotid-femoral PWV, the noninvasive gold standard for measuring PWV [23], in contrast to previous studies that used a wide scale of non-conventional methods for assessing arterial stiffness (augmentation index, brachialankle pulse wave velocity and finger photoplethysmogram) [7,8,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%